Development of folklore teaching materials assisted by digital comics for grade 3 students - Ruth Zelena Simanjuntak; Mara Untung Ritonga; Zulkifli Matondang (Inovasi Kurikulum, 2024)
The learning resources teachers use are inadequate, making students bored, and the absence of innovative planning to improve teaching materials motivates researchers to develop teaching materials. This research aims to determine the validity, practicality, and effectiveness of folklore teaching materials assisted by digital comics. This type of research is research and development (Research and Development) with the ADDIE model, which consists of 5 development stages: Analyze, Design, Development, Implementation, and Evaluation. The subjects in this research were 22 students in class 3B of SD Negeri 101764 Bandar Klippa. Data collection techniques in this research used interviews, observation, questionnaires, and tests. The results of the research show 1) The development of folklore teaching materials assisted by digital comics uses the ADDIE development model, 2) The feasibility test by material experts and the design experts is at a very decent qualification, 3) The practicality test carried out by the class 4B teacher was at a very practical qualification, 4) The effectiveness test showed very effective results as seen from the pre-test results which experienced an increase in the post-test results in each lesson 1, 2 and 3 on students' writing and speaking abilities.   Abtsrak Sumber belajar yang digunakan guru kurang memadai membuat peserta didik menjadi bosan serta tidak adanya perencanaan inovasi untuk memperbaiki bahan ajar memotivasi peneliti untuk melakukan mengembangkan materi ajar. Tujuan dalam penelitian ini yaitu untuk mengetahui validitas, praktikalitas, efektivitas Materi ajar cerita rakyat berbantuan komik digital. Jenis penelitian ini adalah penelitian dan pengembangan (Research and Development) dengan model ADDIE yang terdiri dari 5 tahap pengembangan yaitu : Analyze, Design, Development, Implementation, dan Evaluation. Subjek dalam penelitian ini adalah peserta didik kelas 3B SD Negeri 101764 Bandar Klippa yang berjumlah 22 peserta didik. Teknik pengumpulan data dalam penelitian ini menggunakan wawancara, observasi, kuesioner, dan tes. Hasil penelitian menunjukkan bahwa 1) Pengembangan Materi Ajar cerita rakyat berbantuan komik digital ini menggunakan model pengembangan ADDIE, 2) Uji kelayakan oleh ahli materi dan ahli desain berada pada kualifikasi sangat layak, 3) Uji kepraktisan yang dilakukan oleh guru kelas 4B berada pada kualifikasi sangat praktis, 4) Uji keefektifan menunjukkan hasil sangat efektif terlihat dari hasil pre-test yang mengalami peningkatan pada hasil post-test disetiap pembelajaran 1, 2 dan 3 pada kemampuan menulis dan berbicara peserta didik. Kata Kunci: Cerita rakyat; komik digital; materi ajar; pengembangan